Corrigendum to "Mathematical Modeling of COVID-19 Transmission Dynamics with a Case Study of Wuhan" [Chaos Solitons Fractals 135 (2020), 109846] - Ndaïrou, Faïçal (2020)
We correct some numerical results of [Chaos Solitons Fractals 135 (2020), 109846], by providing the correct numbers and plots. The conclusions of the paper remain, however, the same. In particular, the numerical simulations show the suitability of the proposed COVID-19 model for the outbreak that occurred in Wuhan, China. This time all our computer codes are provided, in order to make all computations reproducible. The authors would like to apologize for any inconvenience caused.